Myiasis in Palate by Cochliomyia hominivorax - Vale, Daniel Santiago; Cavalieri, Irio; Araujo, Marcelo Marotta [UNESP]; Pessoa Santos, Milkle Bruno; dos Santos Canellas, Joao Vitor; Perez Espinola, Lilian Victoria; Breda, Marcus Antonio (Lippincott Williams & Wilkins, 2011)
Myiasis is the infestation of tissues and organs of animals and humans caused by the larvae of certain dipteran flies. It is more common in undeveloped and tropical countries and usually affects elderly patients, persons who are sick, and patients with mental illness. Oral myiasis is a rare pathologic condition and a risk to the patient's life because of its great destructive potential. Therefore, appropriate treatment is necessary. This article aimed to report a case of myiasis caused by Cochliomyia hominivorax in the palate of a patient with primary progressive aphasia, which was successfully treated through mechanical removal of larvae plus administration of ivermectin.
Keywords: Oral myiasis; ivermectin; Cochliomyia hominivorax